2018
DOI: 10.20319/pijss.2018.43.496518
|View full text |Cite
|
Sign up to set email alerts
|

Steam (Science, Technology, Engineering, Art, and Mathematics) Education and Teachers’ Pedagogical Discontentment Levels

Abstract: Literature focused on the emerging implementation of STEAM (Science, Technology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…There can be many challenges to the design and delivery of STEAM education. Educators and education systems have not fully figured out how to deliver an interdisciplinary STEM and STEAM approach (Ejiwale, 2013;Thompson et al, 2018). Consequently, educators struggle with a clear conceptualization of STEAM and how the disciplines might be connected (Guyotte et al, 2015;Quigley and Herro, 2016;Quigley et al, 2017Quigley et al, , 2020.…”
Section: Science Technology Engineering Arts and Mathematics Educatio...mentioning
confidence: 99%
“…There can be many challenges to the design and delivery of STEAM education. Educators and education systems have not fully figured out how to deliver an interdisciplinary STEM and STEAM approach (Ejiwale, 2013;Thompson et al, 2018). Consequently, educators struggle with a clear conceptualization of STEAM and how the disciplines might be connected (Guyotte et al, 2015;Quigley and Herro, 2016;Quigley et al, 2017Quigley et al, , 2020.…”
Section: Science Technology Engineering Arts and Mathematics Educatio...mentioning
confidence: 99%
“…With sufficient support, teachers reported positive effects on their teaching and classroom environments, suggesting STEAM as an impactful intervention (Thompson et al, 2018). STEAM instruction was not without effort, and teachers described undergoing a "mindset shift" necessary to adjust their teaching practices and develop their own content knowledge necessary for STEAM instruction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found positive impacts of sustained teacher professional learning in STEAM on participating teachers and their students (Thompson et al, 2018;Quigley et al, 2019;Conradty and Bogner, 2020;Wong et al, 2023). A study of intensive STEAM interventions suggests that STEAM can have positive effects on teachers and the classroom environment when teachers have ample, ongoing support (Thompson et al, 2018).…”
Section: Steam Professional Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Gugun Geusan Akbar, Dede Kurniadi, The researchers responded to the COVID-19 Pandemic with various efforts made, they seemed to race with time to find a vaccine and how to fight this COVID-19 (S. F. Ahmed, Quadeer, & McKay, 2020;Caddy, 2020;Gao, Tian, & Yang, 2020;Li, Geng, Peng, Meng, & Lu, 2020;Liu et al, 2020;Prompetchara, Ketloy, & Palaga, 2020). However, most experts agree it will be 12-18 months before a coronavirus disease (COVID-19) vaccine is approved, and even longer before one is available on a wide scale (Thompson, Barber, & Bourget, 2018). With the time required for the vaccine to be applied, governments in all countries must have a strategy that can suppress this COVID-19 outbreak.…”
Section: Introductionmentioning
confidence: 99%